Implementation of The Budget Functions of The Regional People's Representative Council, Solok City, West Sumatra Province - Fidowaty, T; Pratama, G D; Majid, Z R (Proceeding of International Conference on Business, Economics, Social Sciences, and Humanities, 2023)
One of the functions of the Regional House of Representatives is the budget function. The budget function includes a discussion of the Regional Revenue and Expenditure Budget. The Regional People's Representative Council discusses and also gives approval to the draft of the Regional Revenue and Expenditure Budget submitted by the regional government. Optimization of the implementation of the budget function will be related to the implementation of development and good governance This study aims to determine the implementation of the budget function of the Solok City Regional House of Representatives in the preparation of the 2020 Solok City Regional Revenue and Expenditure Budget. The method that the researcher uses is descriptive method through a qualitative approach. Data collection techniques used literature studies and field studies consisting of observation and in-depth interviews. The results show that the implementation of the budget function by the Regional People's Representative Council has not been running effectively and efficiently in the absorption of budget use, yes, this is seen from the not yet maximal implementation of the program in every organization and regional apparatus in Solok City. There have been many budget cuts and diversions that have been set previously because the budget is used to handle the Coronavirus Disease-19 (Covid-19) pandemic that is hitting Indonesia. The impact of this research is to become a concern for the government and become knowledge in government science for future researcher.